Optimization of biosorptive removal of cobalt(ii) onto eucalyptus globulus L. - D. HYMAVATHI,; DR G. PRABHAKAR, (International Journal of Pharma and Bio Sciences, 2017)
The objective of this study is to evaluate the efficacy of Eucalyptus globulus leaf powder in the removal of Cobalt(II) from aqueous solutions. Detailed batch mode experimentation using Response Surface Methodology (RSM) is undertaken and at optimum conditions, the maximum biosorption capacity of E. globulus leaf powder for Cobalt(II) loading is qmax = 7.194 mg/g. Freundlich equilibrium model is identified for adsorption process, after trying three standard isotherm models - Langmuir, Freundlich and Temkin isotherms. Pseudo-second-order kinetic model describes the adsorption process. Surface morphology studies through Fourier Transform Infrared Spectroscopy[FTIR] and Scanning Electron Microscopy [SEM] with Energy Dispersive X-ray spectroscopy(EDX) confirms the metal loading on the adsorbent surface.